Efecto tectónico del Terremoto de Limón - Denyer, Percy (2011)
In this paper we analize the superficial tectonic effect in the southeastern Caribbean region of Costa Rica, which was directly related to the Limón earthquake of April-22, 1991. A preliminar palco-seismic approach is based on several profiles and sketehes of the shoreline. The most dramatic tectonic was the uplifting of the shoreline, from Moin, in the north, to Gandoca, in the south. Three secondary faulting zones were mapped, and they slipped during the earthquake: Rio Blanco, La Estrella and Sixaola faulting zones. These co-seismic faults represent different steps in the evolution of faullting in the basement. They were mapped on non-consolidated sediments. These structural features could he faults, that were re-actived during the earthquake, causing the segmentation of the hanging wall which moved to the northeast. We observed abundant geologic evidence of large pre-1991 uplifl events along the same strech of Caribbean coast affected by the Limón earthquake.